(untitled) (Journal of Universal Science Research, 2025)
Integrating child and adolescent hygiene principles in preschool institutions is essential for promoting long-term health, preventing disease, and fostering lifelong hygiene habits during critical developmental years. Preschool years are a formative period in a child’s physical, emotional, and social development. During this time, children begin to acquire habits that can impact their health throughout life. Proper hygiene in preschool settings not only prevents the spread of infectious diseases but also lays the foundation for healthy behaviors.